Interprétations psycho-culturelles de l’inadaptation juvénile dans la société de masse contemporaine - Szabo, Denis; LeBlanc, Marc; Deslauriers, Lise; Gagné, Denis (Acta Criminologica)

(untitled) (Les Presses de l'Université de Montréal, 1968)
AbstractA PSYCHO-CULTURAL INTERPRETATION OF JUVENILE MALADJUSTMENT IN MASS SOCIETY Juvenile maladjustment in the post-industrial societies has not only augmented alarmingly but has also taken on a new dimension. The number and seriousness of offences as well as their obvious wantonness are increasing. This article is an attempt to understand the forces which engender this phenomenon. A first experiment in measuring some of the elements which constitute the moral fact is also described here. A culture conflict Maladjustment of the young in the mass society can be looked at in the perspective of a culture conflict, that is, the confrontation of morals between adult and youth in a society undergoing an historical acceleration not only of its technology but also of its institutions and culture. The dialectic, youth versus adult, is due to the fact that each group has a particular position in society which, therefore, implies different morals or different normative systems. The credo of the adult is founded upon a numerous variety of experiences marked by success or failure. This traditional morality will shift in direct proportion to the degree of evolution within the existing society. The morals of youth are founded upon its involvement in new experiences. Youth uses the technology of its era, rebels against old-fashioned morals and reformulates its ethical needs. This type of questioning leads the adult to ambiguity of values, to uncertainty of moral judgment and to a wavering in fundamental choices; it leads the young into contesting adult order, truth and conviction. The integration of youth into mass society has to be made in the light of « neotenistic » mechanisms of adjustment to innovation. It must also be examined in the light of « misoneism » — resistance to change .— as well as of stability of social relationships and institutions. The young, new citizens of a mass society and trustees of mass culture, have to cope with the institutions, ideologies, controls and rules forged by a society of production. Psycho-cultural pressures Recent social transformations have generated a new type of society known as the « mass society » which in turn has generated a « mass culture ». The interaction between culture and society creates, for the individual, new problems of adjustment which merit careful study. The relative freedom from the pressures of mechanization coincides with the increase of psycho-cultural pressures due to the means of mass communication. We require a new conceptual plan of analysis adapted to a different type of society. The theories based on culture conflicts, the concepts of subcultures and contracultures have attempted to explain these new phenomena. Today, external pressure has increased the possibility of choice for the individual. We might suggest therefore, that if the maladjustments of the past were due to the hide-bound socio-economic laws, those which characterize the mass society would be due to an extreme degree of freedom to make these numberless choices. Obligation: first foundation of morals Psycho-cultural analysis achieves its entire meaning when we study morals or the moral fact. In other words, the obligation to accomplish one act or another constitutes the main springboard for interaction within a social system. The moral fact, in its objective and subjective aspects, constitutes the core of the problem: how to explain that the very foundation of moral order is being radically and universally questioned ? To answer this, we must use an analysis of mechanisms and procedures which take precedence in internalizing moral values in different cultures. The questions asked are as follows : a) What is the content and meaning of obligation to the youth of today ? b) What is the relationship between its aspirations and those of the preceding generations ? c) Are these aspirations the same for the youth of different classes ? d) Do they then engender cultures, subcultures and contracultures ? Psycho-cultural analysis is the meeting point of questions asked by the sociology of knowledge and of socialization and by contemporary social psychology. The moral fact seems to be an integral part of the problem of man's maladjustment to the civilization he has created, and its study becomes necessary in order to find the key to certain paradoxes in the human condition. Measurement of the moral fact Psycho-cultural interpretation seeks to isolate maladjustment, regarding it essentially as a type of moral behaviour. If we accept the following postulate — adjustment or deviance results at the limit of conformity or non-conformity to values .— how do we measure this obligation ? What are the variables necessary to isolate this idea of obligation ? What are the instruments capable of measuring them ? In the context of our work, obligation is envisaged, on the one hand, as a normative system related to the position of an individual, of a collectivity or of a category of individuals, in the social structure. On the other hand, it is regarded as a physical function, representing the internal controls of the subject, who is submitted to a system of impulses and motivations. Two theories seem pertinent in explaining obligation: the theory of « moral conscience », related to subjective motivations, and the theory of « social character », related to substantive or group motivations. According to Erick Fromm (1949), every society and every social structure within the society forms the type of man it needs and transmits values, attitudes and motivations necessary for the individual to act out the role it expects him to. It accomplishes this by giving the individual a « social character » adapted to its demands and which enables the subject to behave in the manner called for by the social system. The hypothesis showing that the social character is formed by the role the individual plays in his own culture and that he reflects collective obligations individually, enables us to connect this problem of adjustment with socio-cultural controls. Thus we can suppose that the normative aspects of adolescent subcultures and contracultures, where they exist, form a social character in these young people, and so constitute a different source of orientation or obligation from that of the adult culture. This article gives an account of the construction and validity of scales of moral attitudes and of an implement capable of measuring certain aspects of the moral conscience. Their function is to isolate this idea of obligation. Five scales of moral attitudes were established and verified with the help of factoral analysis .— moral attitudes of authority, of conformity to peers, of aspiration, of hedonist anxiety and of self-evaluation. This scale discriminates between the socio-economic milieux of the working class and the leisure class and weighs the variables .— age and delinquency. If social character is the cultural counterpart of obligation, then moral conscience is the psychological counterpart. Whereas social character depends on the position of a group in the social structure, moral conscience is conditioned by interprofessional relationships. Seen in this light, moral conscience becomes a psychic function, the fruit of identification within a succession of values presented by parents, teachers and peers. Since it is almost impossible to measure moral conscience directly and experimentally by objective tests, we thought it best to measure the psychological procedures of transmission and internalization of moral values, that is, by perception and identification. The Role Construction Repertory Test of George A. Kelly (1955) seems to answer this problem because it is based on these two psychological mechanisms as well as on « role playing ». This test enables us to find out with which persons and what values adolescents identify, whether or not they are well adjusted to life in society. It also enables us, with the help of the construction analysis, to pin-point the image young people have of themselves and of those who make up their phenomenal or experimental universe. These instruments, tested on adjusted or maladjusted adolescents from different socio-economic milieux, will enable us to verify certain hypothesis resulting from psycho-cultural analysis.